2022
DOI: 10.1155/2022/2615580
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Clinical Efficacy and Molecular Mechanism of Xuefu Zhuyu Decoction in the Treatment of COPD Based on Meta-Analysis and Network Pharmacology

Abstract: Background. Chronic obstructive pulmonary disease (COPD) is becoming a major public health burden worldwide. It is urgent to explore more effective and safer treatment strategy for COPD. Notably, Xuefu Zhuyu Decoction (XFZYD) is widely used to treat respiratory system diseases, including COPD, in China. Objective. This study is aimed at comprehensively evaluating the therapeutic effects and molecular mechanism of XFZYD on COPD. Methods. Original clinical studies were searched from eight literature databases. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Most of the Chinese medicines used in the treatment of COPD through the regulation of PI3K/Akt signaling pathway are based on "warming the lungs and kidneys, expelling drinks and removing blood stasis", which reflects the concept of "combination of tonic and tonic" in Chinese medicine, warming the kidneys and boosting yang, transforming the cold drinks and removing the stasis of blood, and then all the symptoms will be relieved. The Chinese medicines that are used more frequently are Huang Qin, Dang Shen, Ban Xia, Fu Ling, Chen Pi, Gan Cao, Huang Qi et al [54][55][56][57][58][59][60] which are of good application value and prospect in the prevention and control of COPD, providing the direction of the use of Chinese medicine in the treatment of COPD, providing new ideas and methods for the treatment of COPD, which is of certain significance, and providing theoretical foundations for the use of medicines in the future clinic and the direction of the research of COPD. However, the clinical effectiveness of Chinese medicine in treating COPD has been confirmed and widely accepted, but the research on the mechanism of PI3K/Akt signaling pathway on COPD is still in the early stage, and there are fewer clinical studies on the treatment of COPD through this pathway, and the intervention in the PI3K/Akt signaling pathway in the treatment of COPD is mostly confined to the animal experiments and the cellular level, so the development of related clinical research is the direction of future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the Chinese medicines used in the treatment of COPD through the regulation of PI3K/Akt signaling pathway are based on "warming the lungs and kidneys, expelling drinks and removing blood stasis", which reflects the concept of "combination of tonic and tonic" in Chinese medicine, warming the kidneys and boosting yang, transforming the cold drinks and removing the stasis of blood, and then all the symptoms will be relieved. The Chinese medicines that are used more frequently are Huang Qin, Dang Shen, Ban Xia, Fu Ling, Chen Pi, Gan Cao, Huang Qi et al [54][55][56][57][58][59][60] which are of good application value and prospect in the prevention and control of COPD, providing the direction of the use of Chinese medicine in the treatment of COPD, providing new ideas and methods for the treatment of COPD, which is of certain significance, and providing theoretical foundations for the use of medicines in the future clinic and the direction of the research of COPD. However, the clinical effectiveness of Chinese medicine in treating COPD has been confirmed and widely accepted, but the research on the mechanism of PI3K/Akt signaling pathway on COPD is still in the early stage, and there are fewer clinical studies on the treatment of COPD through this pathway, and the intervention in the PI3K/Akt signaling pathway in the treatment of COPD is mostly confined to the animal experiments and the cellular level, so the development of related clinical research is the direction of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium tanshinone IIA sulfonate is a water-soluble substance obtained by sulfonation of the diterpene quinone compound tanshinone isolated from Salvia miltiorrhiza (S. miltiorrhiza), which possesses a variety of biological activities such as antioxidant, antibacterial and anti-inflammatory, anticoagulant effects and inhibition of airway remodeling [30] . Wang et al [31] found that tanshinone IIA sodium sulfonate, an extract of S. miltiorrhiza, reduced serum TNF-α, IL-1β, IL- Cryptotanshinone Diterpene (chemistry) U937 cells ↓Akt levels, ↑HDAC2 protein levels [58] mRNA. Its mechanism may be related to its ability to down-regulate the expression of PI3K, AKT1 mRNA and up-regulate the expression of mTOR mRNA.…”
Section: Intervention Of Pi3k/akt Signaling Pathway By Tcm In Copd Tc...mentioning
confidence: 99%
“…Notably, Bu-Shen-Fang-Fang-Chuan formula (BSFCF), a commonly used formula for treating COPD in China, attenuates the inflammatory response to COPD by inhibiting PI3K/Akt-Nrf2 and PI3K/Akt-NF-κB (Li Q. et al, 2020). Xuefu Zhuyu Decoction (XFZYD) is also widely used in the treatment of COPD, and (Hu et al, 2022) and others have found that XFZYD is effective in the treatment of COPD by interfering with the PI3K/ Akt signaling pathway, improving oxidative stress and inflammatory responses, and relieving airway remodeling and ventilation disorders through web-based pharmacology and molecular docking experiments. In addition, Tiaobu Feishen (TBFS) was observed to reverse lung inflammation and airway remodeling (Li et al, 2012), observed that TBFS has more effective in glucocorticoid-resistant COPD patients by modulating PI3K/Akt signaling to improve glucocorticoid resistance.…”
Section: Othersmentioning
confidence: 99%
“…Notably, Bu-Shen-Fang-Fang-Chuan formula (BSFCF), a commonly used formula for treating COPD in China, attenuates the inflammatory response to COPD by inhibiting PI3K/Akt-Nrf2 and PI3K/Akt-NF-κB ( Li Q. et al, 2020 ). Xuefu Zhuyu Decoction (XFZYD) is also widely used in the treatment of COPD, and ( Hu et al, 2022 ) and others have found that XFZYD is effective in the treatment of COPD by interfering with the PI3K/Akt signaling pathway, improving oxidative stress and inflammatory responses, and relieving airway remodeling and ventilation disorders through web-based pharmacology and molecular docking experiments. In addition, Tiaobu Feishen (TBFS) was observed to reverse lung inflammation and airway remodeling ( Li et al, 2012 ), Zhou et al (2023) observed that TBFS has more effective in glucocorticoid-resistant COPD patients by modulating PI3K/Akt signaling to improve glucocorticoid resistance.…”
Section: Potential Drug Targeting Pi3k/akt For Copdmentioning
confidence: 99%